"Men Don't Like to Work Under a Woman": Female Chemists in the Photographic Manufacturing Industry, ca. 1918–1950. (3rd July 2022) - Mercelis, Joris
Abstract : Around the start of the 1920s, the situation of female chemists in the photographic manufacturing industry was literally and figuratively explosive, for their record in conducting hazardous organic syntheses made the research director of the largest photographic firm conclude that chemistry was not an appropriate field for women. About two decades later, by contrast, the photographic industry had developed into one of a relatively small number of industries where female chemists had obtained recognition and promotions not only as librarians, patent professionals, and chemical analysts but also as experimental and theoretical investigators in research and development laboratories. This article suggests that to make sense of this turnabout, it is crucial to carefully examine the position of women chemists in corporate organisational structures and hierarchies, including the possible unintended consequences of segregating women into separate scientific labs and/or teams. This study's findings also point to the value of using scientific groups and labs as units of analysis in historical research on women scientists in industry, an approach that could be extended to other cases and might help stimulate more dialogue between historians of corporate science and R&D on one hand and historians of women and gender in science on the other.